Hospitalization Rates for Inflammatory Bowel Disease Are Decreasing Over Time: A Population-based Cohort Study - Buie, Michael J; Coward, Stephanie; Shaheen, Abdel-Aziz; Holroyd-Leduc, Jayna; Hracs, Lindsay; Ma, Christopher; Panaccione, Remo; Benchimol, Eric I; Bernstein, Charles N; Bitton, Alain; Otley, Anthony R; Jones, Jennifer L; et al. (Inflammatory bowel diseases, 2023)
Background Recent advances in the management of inflammatory bowel disease (IBD) striving for new treatment targets may have decreased rates of hospitalization for flares. We compared all-cause, IBD-related, and non-IBD-related hospitalizations while accounting for the rising prevalence of IBD. Methods Population-based, administrative health care databases identified all individuals living with IBD in Alberta between fiscal year 2002 and 2018. Hospitalization rates (all-cause, IBD-related, and non-IBD-related) were calculated using the prevalent Alberta IBD population. Hospitalizations were stratified by disease type, age, sex, and metropolitan status. Data were age and sex standardized to the 2019 Canadian population. Log-linear models calculated Average Annual Percentage Change (AAPC) in hospitalization rates with associated 95% confidence intervals (CIs). Results From 2002-2003 to 2018-2019, all-cause hospitalization rates decreased from 36.57 to 16.72 per 100 IBD patients (AAPC, −4.18%; 95% CI, −4.69 to −3.66). Inflammatory bowel disease–related hospitalization rate decreased from 26.44 to 9.24 per 100 IBD patients (AAPC, −5.54%; 95% CI, −6.19 to −4.88). Non-IBD-related hospitalization rate decreased from 10.13 to 7.48 per 100 IBD patients (AAPC, −1.82%; 95% CI, −2.14 to −1.49). Those over 80 years old had the greatest all-cause and non-IBD-related hospitalization rates. Temporal trends showing decreasing hospitalization rates were observed across age, sex, IBD type, and metropolitan status. Conclusions Hospitalization rates are decreasing for all-cause, IBD-related, and non-IBD-related hospitalizations. Over the past 20 years, the care of IBD has transitioned from hospital-based care to ambulatory-centric IBD management. Lay Summary Hospitalization rates per 100 IBD patients are decreasing. However, when using the general population as the denominator, the interpretation of temporal trends changes because the prevalence of IBD has risen faster than the general population’s growth rate. Graphical Abstract